Some Midpoint Inequalities for η-Convex Function via Weighted Fractional Integrals. (12th January 2022) - Chen, Lei; Nazeer, Waqas; Ali, Farman; Botmart, Thongchai; Mehfooz, Sarah
Abstract : In this research, by using a weighted fractional integral, we establish a midpoint version of Hermite-Hadamrad Fejér type inequality for η -convex function on a specific interval. To confirm the validity, we considered some special cases of our results and relate them with already existing results. It can be observed that several existing results are special cases of our presented results.